2018
DOI: 10.1589/jpts.30.286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of expiratory muscle training on the frail elderly’s respiratory function

Abstract: [Purpose] The present study examined the effects of expiratory muscle training on elderly day care service users, who had been classified into Care Grades 1 and 2 based on Japan’s long-term care insurance system. [Subjects and Methods] Intervention was provided for 29 Care Grade 1 or 2 day care service users. During intervention, expiratory muscle training was performed by slowly expiring using the abdominal muscles and a device after maximal inspiration. Each intervention session lasted for approximately 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, these studies were carried out using an expiratory pressure threshold device. A recent study [30] observed favorable effects of forced expiratory training on vital capacity and peak expiratory flow in frail and elderly subjects. In this study, the subjects practiced slow expiration using abdominal muscles and a resistance device for 20 min/day in 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were carried out using an expiratory pressure threshold device. A recent study [30] observed favorable effects of forced expiratory training on vital capacity and peak expiratory flow in frail and elderly subjects. In this study, the subjects practiced slow expiration using abdominal muscles and a resistance device for 20 min/day in 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IMT has been recommended as a part of pulmonary rehabilitation programs for patients with COPD [ 5 , 6 ]. Expiratory muscle training (EMT) can improve vital capacity and peak expiratory flow [ 7 , 8 ], which are also beneficial for cough function. In addition, the improvement in cough function is a vital part of pulmonary rehabilitation; therefore, RMT including IMT and EMT plays a critical role in the management of COPD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%